Capacity Building Training for Administrators to Improve the Management of Harapan Makmur Village-Owned Enterprise in Tebing Tinggi Village: Pelatihan Peningkatan Kapasitas Pengurus dalam Rangka Meningkatkan Pengelolaan BUMDES Harapan Makmur Desa Tebing Tinggi - Anthony Hamzah; Angga Pramana; Eko Wahyudi; Rahmadini Payla Juarsa; Jeany Ristia; Chandra Gunawan; Nur Hasnah; Vivin Jenika Putri; Anania Rahmah; Arum Rovarti Ningsih; Nadya Novianti Dwi Putri; Addiena Syahvina Nasution; Masyitah; Fikratul Ikhsan; Fadlila Endyra (Universitas Lancang Kuning, 2025)
BUMDes Harapan Makmur was established with the aim of developing the village's economic potential through business units based on local resources, including the management of agricultural tools, trade in agricultural products, and equipment and transportation rental services. The businesses run by BUMDes have not yet been operating optimally. This is due to a lack of competent human resources, a lack of external support, and limited access to training and outreach at BUMDes Harapan Makmur. This community service program aims to identify strategic steps to increase the capacity of BUMDes management for suntainability. The methods used in the preparation stage included surveys and Focus Group Discussions (FGDs), while the implementation and evaluation stages followed. The training results indicated that BUMDes Harapan Makmur has several potential business units that can be developed, namely the Rice Milling Unit (RMU), a 5-hectare oil palm plantation, agriculture and livestock businesses, oil palm plantations (5 ha) and rice fields (70 ha), provision of agricultural production facilities (saprodi), agricultural services (RMU, rice field plowing), and travel services. Implications in increasing the capacity of administrators through capacity building training for administrators, optimization of agricultural tools and agricultural inputs, socialization and community empowerment